Gender equality social justice and development : the CARICOM Post-Beijing Regional Plan of Action to the year 2000 (CCS GeorgetownGY, 1997)
Addresses the issue of subordination as well as areas of male disadvantage such as levels of participation and performance of some groups of males in education. Speaks to broader issues of social justice, for example, the promotion of the rights of indigenous people and people with disabilities. Indicates that the effective implementation of the plan requires that national and secretariat machinery be strengthened, and that at the national level, the status of the Women's Bureaux be enhanced.
Additional copy located in the Office of the Secretary-General